Strategi Guru PAI dalam Menanamkan Nilai-Nilai Moderasi Beragama pada Siswa di Kabupaten Siak - Edy, Pebri (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2023)
This article describes about Regulation of the Minister of Religious says that religious teachers are required to be able to strengthen religious moderation among students, so PAI teachers in Siak Regency make efforts to foster religious moderation for students through various strategies and certain coaching methods to build religious moderation values. The aims of this study are: First, to describe how the efforts of PAI teachers in fostering religious moderation; Second, to find out the supporting and inhibiting factors in fostering religious moderation. This study uses a descriptive qualitative approach. The results of the study show that the efforts made by PAI teachers in fostering religious moderation are by conducting coaching inside and outside the classroom using strategies and methods. The strategy used is a direct strategy by providing directions, examples, both inside and outside the classroom and an indirect strategy by providing prohibitions and prevention, while the method used is: (a) the method of exemplary by setting a good example for students; (b) the method of providing advice by giving advice before and towards the end of learning; (c) the method of discipline by giving rules; (d) the method of habituation by familiarizing students to attend recitation and apples; (e) the method of giving special attention to pay attention to the development of student attitudes that reflect religious moderation; and (f) the method of punishment by giving sanctions in the form of reducing religious values ​​for students who violate the rules.